ANALISIS PENGARUH FAKTOR PENYEBAB STRES KERJA SECARA INDIVIDUALTERHADAP PRESTASI KERJA KARYAWAN BAGIAN OPERASIONAL PADA PT. SAMUDRA INDONESIA CABANG SURABAYA (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2004)
A personality manager of an organization is demand to produce a competen employee and also can manage all department, although in the accomplishment process is found in conflict between an organization importance and the employee, so that can be influence the work of employee and it caused of their success work. There was a sample of 600 employees in United State of America, which showed that 46 percent of their work was stresfull and 34 percent reported that stres was the worst, so they trought to quite from their job (A. Farnham, "Who Beats Sires Best - and How ", 1991). A variable offactor caused sires individually which can be used in this survey are role conflict, role ambiguity, work exhaustion, and fairness of reward. The result of the survey prove that the first hypothesis can be received. That mean there is a significant between the variable of role conflict, role ambiguity, work exhaustion, and fairness of reward. to the work success of the operational staff in PT. Samudra Indonesia Unit Surabaya. And the second hypothesis is reject, that mean fairness of reward is not a variable which has a dominant influence to the work success of the operational staff in PT. Samudra Indonesia Unit Surabaya, but the role ambiguity is the most dominant.